S05.4 Potential incongruities in relative measures of disparities in sexually transmitted diseases. (13th September 2015) - Chesson, Harrell
Abstract : Sexually transmitted infections (STIs) in pregnancy prevalent in many resource limited settings are associated with adverse pregnancy outcomes that include spontaneous abortion, stillbirths, preterm rupture of membranes, premature delivery and postpartum endometritis. Antenatal clinic attendance provides opportunity to screen the women for STIs, offer prompt treatment for curable STIs or prophylaxis for viral infections such as HIV and to promote prevention. Although routine screening for syphilis and HIV is recommended as part of antenatal care (ANC), optimal screening rates have not been achieved. This is due antenatal clinic non-attendance, non-availability of screening tests and where available, health system inefficiencies such long wait time before test results are available or need for women to make return visits to receive results. Use of point-of care tests that detect syphilis and HIV have been shown to increase the number of women tested for HIV and syphilis, are inexpensive, easy to use and do not require a sophisticated laboratory. In resource limited settings, prompt detection and treatment of the other STIs is hampered by lack of screening tests. Often, health providers rely on syndromic approach to diagnose and manage STIs. This approach alleviates the need for laboratory services but misses women with asymptomatic infections and has poor diagnostic performance. Pregnant women with STIs are at an increased risk of acquiring HIV and transmitting the infection to their infants. Increased availability of HIV testing and provision of effective PMTCT regimens has dramatically reduced the number of new paediatric HIV infections. However, STIs, apart from HIV, have not been viewed as a public health priority and adequate resources allocated to combat them. To optimise maternal and infant outcomes, there is need to prioritise development of low-cost tests to detect STIs during pregnancy and to ensure women are provided with effective treatment promptly.